Prioritas Strategi Pengembangan Industri Halal di Kabupaten Tasikmalaya: Pendekatan Analytical Hierarchy Process - Fitranty Adirestuty; Muhammad Askha Refsanjani; Hilda Monoarfa; Kiki Hardiansyah (Universitas Galuh, 2023)
This research aims for finding the strategy of development the food and beverages industry in the Regency of Tasikmalaya with provide problems and solutions which are relevant and valid. Then, the method used in this research is Analytical Hierarchy Process with Superdecision as an analysis tool. The subject in this present research is the experts who are relevant to the research’s purpose governor, academics, and practitioners. There are seven experts who are collected by the researcher. The results of the research indicate that the most problem in the aspect’s dimension is regulation, on the other side, the most problem in the indicator dimension is that producers of food and beverages are less halal awareness and lack the capacity for halalness products. And then, the highest solution priority is the infrastructure aspect and there are two the highest solution priority in indicators which are Training and Socialization from Governor to Halal Food Beverages Industry and Sharia Bank is act for promoting on Food and Beverages Industry about credit of shariah which is acceptable.